Data of age- and gender-related physical and coordination abilities as normative for drivers in the area of health and safety. (September 2020) - Roman-Liu, Danuta; Mazur-Różycka, Joanna; Tokarski, Tomasz
Abstract: Purpose: The aim of this study was to provide normative data measures of upper and lower limb strength, body balance and coordination, taking into account differences related to age and gender. Materials and methods: The study included four groups of 60 people, differentiated by gender and age. During the tests, moments of strength in the joints of the upper and lower limbs, maintenance of body balance, and the coordination of upper and lower limbs were measured. Results: Both age and gender had a significant impact on most of the measures characterising maximum strength capacity. In the case of body balance, only age differentiates the measures, while the measures determining coordination were more diverse due to gender. Statistically significant correlations were found between the moments of upper limb strength and the measures of coordination of the upper limb. Fewer such statistically significant correlations were found for the lower limb. There are no statistically significant correlations between muscle strength and variables characterising body balance. Results present the influence of age and gender on the ratio of the proportions of antagonistic muscle groups; and the relationship between measures of muscle strength, balance and coordination. Analysis were done within age and gender groups. Conclusion: Strength capabilities of the upper and lower limbs are strongly diversified due to age and gender. It can be assumed that the strength of the lower limb muscles is not the dominant factor determining the maintenance of body balance. It can be argued, however, that the ratio of the moment of force of flexors and extensors in the hip joint can be meaningful. The presented results can be used as age-specific normative data for ergonomic assessment of professional drivers and for consideration of those values in the design process of motor vehicles and driving simulators. Highlights: Ratio of antagonistic muscles strength differs by age and gender. Older drivers have not worse lower limb coordination abilities comparing to young. Relationship between coordination abilities and muscle strength is very week. Ratio of hip flexors and extensors strength is the dominant factor in balance control. Body balance is diversified due to age and gender and coordination due to gender.